(untitled) (Research, Society and Development, 2025)
Dental anomalies are common findings in patients with Down syndrome, directly influencing the oral health and quality of life of these individuals. The relevance of this study lies in the need for an in-depth understanding of the specific orofacial and dental characteristics observed in patients with Down syndrome (DS), considering the significant prevalence of malocclusions, maxillary hypoplasia and periodontal diseases. The objective was to review dental anomalies in patients with Down syndrome. This research consists of an integrative literature review, which is an appropriate method to perform a systematic analysis of a specific problem within the scientific field, allowing the identification of gaps in existing knowledge. Patients with Down syndrome have a high prevalence of dental anomalies, such as hypodontia, taurodontism and changes in the chronology of dental inheritance, reinforcing the need for dental follow-up. In addition, there is a significant incidence of malocclusions, anterior open bite and periodontal problems, which, associated with muscle hypotonia and motor difficulties, can compromise masticatory function and adequate oral hygiene, highlighting the importance of early interventions and multidisciplinary planning.